Poverty, vulnerability and food insecurity in Thailand - Bumrungkit, Siraprapa (Curtin University, 2014)
This study analyses the status and determinants of households' vulnerability to poverty and food insecurity in Thailand. Using the expected poverty approach with cross-sectional household consumption data to measure vulnerability the study creates vulnerability profiles within the context of poverty and food insecurity and investigates the impact of crisis-related shocks on poverty. Educational attainment and cultivated land size are found to be the most important factors influencing household's vulnerability to poverty and food insecurity.